Nuclear Law: The Global Debate - Maryam Siddiq Baba (CISS Insight Journal, 2025)
The book Nuclear Law: The Global Debate is a significant and timely addition to the literature on nuclear governance. Rooted in the discussions of the International Atomic Energy Agency’s (IAEA) First International Conference on Nuclear Law in 2022, this edited volume, compiled by the IAEA, is thematically organized to underscore the agency’s pivotal role and the multifaceted nature of the legal frameworks governing nuclear activities worldwide. The book presents a thoughtfully assembled collection of essays that explore the current and future challenges of nuclear law in a rapidly evolving technological and geopolitical context.